Drive Sources Used in the Automotive Industry and Their Impact on Environmental Pollution - Andrzej JAMROZ; Mikołaj WIKTOR (Communications of International Proceedings, 2021)
The automotive industry is one of the branches of the economy whose impact on environmental pollution is enormous. The article analyses the number of pollutants that end up in the natural environment during the production and operation of internal combustion, hybrid, and electric cars. An attempt was also made to decide which type of drive is the most ecological and in which direction the development of the automotive industry should go. The study focused mainly on CO2 emissions because it is a greenhouse gas that does not pose a direct threat to the environment and health of living organisms, but its excess in the atmosphere poses a serious threat to the balance of ecosystems around the world. The results obtained as a result of the analysis confirm the thesis that electric cars are less harmful to the environment than vehicles powered by internal combustion engines. Nevertheless, electrically powered vehicles cannot be called eco-friendly. The problem still lies in the processes of generating electricity, which can be seen in the case of China, where coal is still the most used for this purpose, which generates huge amounts of pollution.  Another problem is the batteries installed in electric cars.  The process of their production is still very energy-consuming, and the complicated structure makes their disposal difficult.
Keywords: Drive; internal combustion engine; electric engine; hybrid; emission of pollutants.